Survey on Acceptance of High Visibility Clothing among Motorcyclists - S. T. M. S. Tajul Arif; M. M. A. Manan; N. M. Khaidir; N. S. M. Zulkiffli (Journal of the Society of Automotive Engineers Malaysia, 2022)
Studies had shown that wearing High Visibility Clothing (HVC) such as safety vests can improve motorcyclists' safety. However, a study by Abdul Manan indicated that only 0.33% wear HVC when riding a motorcycle during the day. Therefore, this study evaluates motorcyclists' acceptance and view of HVC. Survey questions were posted on social media and chat groups to get a response from motorcyclists. The response indicated that among the main reasons for not acquiring or owning HVC were that there are not see the benefit of HVC (37%), did not know where it is sold (24%) and HVC is not affordable (14%). While the response in terms of the main reasons for not wearing HVC is 19% wanted to depart quickly, 18% said it is hot wearing HVC and 13% responded that HVC's design is not looking nice. While 65% either agree or strongly agree that they can easily be seen by other road users when riding during the night, however, 91% and 92% either agree or strongly agree that road users can easily see motorcyclists wearing HVC and wearing HVC can improve visibility during the night and reduce crash risk respectively. This indicates that respondents agree that HVC improves visibility however most did not wear it due to several reasons highlighted in this paper. Therefore, several options may be explored in the future by considering the views of motorcyclists to design and develop HVC that can encourage the wearing rate and thus improve motorcyclists’ visibility and safety.